Patients' and Parents' Concerns over Orthodontic Treatment during the COVID - 19 Pandemic - Magda Trinajstić Zrinski; Petra Anić; Željana Matošić; Sandra Anić Milošević; Senka Meštrović; Marina Lapter Varga (University of Zagreb. School of Dental Medicine, 2024)
Objective: We aimed to assess the impact of the COVID-19 pandemic on the concern of adolescents in orthodontic treatment, and to determine whether personality traits and parental perception were predictors of adolescent patients' concerns. Participants and methods: The sample consisted of 229 adolescent patients (57.2% female) and 223 parents (65.1% female). Questionnaires included items about the importance of infection control and concern about treatment duration and results. Their latent structure was determined using exploratory factor analysis. The Big Five Inventory was used for assessing personality traits. Predictors of patients' and parental orthodontic concern and awareness of the importance of infection control measures were tested by the hierarchical multiple regression analysis. Results: Two factors were revealed for the patient questionnaire, Treatment concern (TC) and Awareness of the importance of measures (AM), and four factors for the parent questionnaire, Parents' treatment concern (PTC), Parents' awareness of the importance of measures (PAM), Parents' concern about the pandemic (PCP) and Parents' concern about their child with regards to the pandemic (PCC). Adolescents' personality traits were not predictors of either TC or AM. PTC was a predictor of TC (p<0.001), accounting for 28% of the variance. PAM and the patient's following of the news were predictors of AM (p≤0.022), accounting for 24% and 2% of the variance, respectively. Conclusion: Parental concern and awareness of measures had an important role in attitudes of adolescent orthodontic patients during the COVID- 19 pandemic, while personality traits did not. The clinician should put additional emphasis on communication with the parent.